A Behavioral Study on the Bornean Orangutan (Pongo pygmaeus) in a Semi-wild Environment at Bukit Merah Orang Utan Island, Perak - Abdullah, Nur Izzati; Dharmalingam, Sabapathy; Md- Zain, Badrul Munir (Journal of Sustainable Natural Resources, 2021)
Although orangutan (Pongo pygmaeus) is one of Malaysian iconic species, however when compared to other great apes this species is not well studied. Several good articles regarding this species in captivity are relatively limited. Due to this reason, a behavioral study of this orangutan (P. pygmaeus) was conducted at Orang Utan Island, Bukit Merah, Perak. The main objectives of this study were to understand the ethology of orangutan in a semi-wild condition and the space utilization of the orangutans that would help in giving picture of the animal’s arboreal and terrestrial nature. Preliminary observations were carried out for five days in January 2016 and intensive observations was carried out for a month in February 2016. The observation method used was focal sampling with continuous reading. The observations were done by focusing on one individual subject for every one hour from 09:00 a.m. to 13:00 p.m. and from 14:00 p.m. to 17:00 p.m. The behavioral profile of the orangutans in semi-wild environment showed that resting, feeding, and playing are the three major daily activities of the orangutans on the island. In accordance with the purpose of this study, the result of the behavioral activities of orangutan can be used for the management and well-being of the orangutan in the study site. It is much hoped with the provided information this will help to increase our understanding of orangutans’ behavior in a semi-wild condition.